Time Domain Measures Of Heart Rate Variability In Heavy Workers - Mithun, Sangita; Begum, Noorzahan; Ferdousi, Sultana; Begum, Shelina; Ali, Taskina (Journal of Bangladesh Society of Physiologist, 2012)
Background: Physical inactivity and low resting heart rate variability (HRV) are associated with increased incidence of coronary heart disease. Heavy physical activity is associated with higher heart rate variability and reduces the risk of coronary heart disease Objective: To assess some time domain measures of HRV in order to compare Cardiac Autonomic Function between sedentary and heavy workers. Methods: This cross sectional study was carried out in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University between 1st July 2008 to 30th June 2009 on 30 apparently healthy heavy workers aged 28-50 years from low socioeconomic condition (study group). For comparison 30 age, sex, BMI and socioeconomic status matched apparently healthy sedentary subjects (group A) were also studied. The study subjects were selected among rickshaw-pullers living in the slum areas nearby BSMMU, Dhaka and the controls were from fourth class employee of BSMMU, Dhaka. Heart Rate Variability were assessed by a Polygraph. Several time domain measures of HRV such as mean R-R interval, mean HR, SDNN, RMSSD were analyzed. For statistical analysis, Independent-Samples t-test, and Pearson’s correlation coefficient tests were done as applicable. Results: Resting mean heart rate (P<0.01), SDNN (P<0.01) and RMSSD (P<0.001) were significantly lower but mean R-R interval (P<0.001) was significantly higher in heavy workers than those of sedentary control. The mean R-R interval (P<0.05) showed significant positive correlation in heavy workers but significant negative correlation in sedentary workers with BMI. Conclusion: Cardiac autonomic nerve function status may be higher with parasympathetic dominance by increased physical activity. DOI: http://dx.doi.org/10.3329/jbsp.v6i2.9755 JBSP 2011 6(2): 77-83